Fairness based channel borrowing strategy for multimedia LEO satellite communications - HUANG Fei; XU Hui; WU Shi-qi (Tongxin xuebao)
A LEO satellite mobility model and user multimedia traffic model was first built,then a novel channel bor-rowing strategy（CBS）was proposed and its performance was evaluated and compared with several existing channel al-location schemes through computer simulation.Simulation results show this scheme can satisfy the QoS requirement of LEO satellite multimedia service very well,at the same time,keeping resource utilization high,finally discussed the fair-ness and system performance under three different channel borrowing strategies.